190k views
4 votes
If ƒ(x) = x − 4 and g(x) = 3x + 5, find (ƒ + g)(x).

User MrJalapeno
by
5.6k points

2 Answers

11 votes

Answer:

please refer to the above attachment


\boxed{(4x + 1) \: is \: the \: right \: answer.}

If ƒ(x) = x − 4 and g(x) = 3x + 5, find (ƒ + g)(x).-example-1
User Sjlver
by
6.9k points
4 votes

Answer:


(f+g)(x)=4x+1

Explanation:

We are given the two functions:


f(x)=x-4\text{ and } g(x)=3x+5

And we want to find:


(f+g)(x)

This is equivalent to:


=f(x)+g(x)

By substitution:


=(x-4)+(3x+5)

Rearranging yields:


=(x+3x)+(-4+5)

Combine like terms:


=4x+1

Hence:


(f+g)(x)=4x+1

User Skip Suva
by
5.7k points